Disc degeneration induces a mechano-sensitization of disc afferent nerve fibers that associates with low back pain. Issue 11 (November 2019) - Park, E.H.; Moon, S.W.; Suh, H.R.; Hochman, S.; Lee, M.-G.; Kim, Y.I.; Jang, I.T.; Han, H.C.
Summary: Objective: We aimed to investigate mechano-sensitivity at the afferent nerve fibers projecting to degenerated intervertebral disc (IVD) and nociceptive behaviour in a rat model of low back pain (LBP). Design: Animal model with LBP was established by lumbar 4/5 IVD puncture and nucleus pulposus aspiration. In vivo single nerve recordings ( n  = 121) were introduced to measure discharge frequency at the afferent nerve fiber innervating the IVD during mechanical stimulations (von Frey filament or intradiscal pressure). Nerve growth factor (NGF) expression levels in the IVD ( n  = 20) were assessed by Western blot. LBP-related behaviour ( n  = 22) was assessed by measuring changes in rearing, mechanical paw-withdrawal threshold, and dynamic weight bearing in a freely walking rat. Inhibitory effect of morphine on the neuronal excitability ( n  = 19) and painful behaviour ( n  = 28) was also assessed. Results: Compared to those with sham or naïve IVD, animal group with degenerated IVD displayed the sensitized neuronal responses and painful behaviour, with hyperexcitability of the afferent nerve fibers in any range of mechanical stimulations (von Frey filament stimulation; 1, 2, and 26 g; intradiscal pressure, 1, 500–3, 000 mm Hg), strong upregulation of NGF (200–250 % increase), and LBP-like behaviour such as failure of rearing, front limbs-dependent walking pattern, and hypersensitivity in hind-paws. However, the neuronal hyperexcitability and pain behaviour were attenuated after local (30 μM) or systemic (3 mg kg −1 ) morphine administration. Conclusions: Our study suggests that enhanced mechano-sensitivity at the afferent nerve fiber innervating degenerated IVD is deeply correlated with LBP development, which supports the hypothesis that hyperexcited responses at the nerve fibers represent a decisive source of LBP.